Application of PON Technology in Video Monitoring Network System - Jun Zhu; Guorong Wang (Dianxin kexue)
This paper analyzes the evolution of video technology, studies of analog and digital development of network technology, analyzes the advantages and disadvantages comparison of different network technology, describes using the city optical network based on PON technology has more advantages in the application of video monitoring network system. At the same time, it is concerned about the operation and maintenance and technical problems and explore solutions of PON to carry video system.